Case Report: Treatment of Kratom Use Disorder With a Classical Tricyclic Antidepressant - Vento, Alessandro E.; de Persis, Simone; De Filippis, Sergio; Schifano, Fabrizio; Napoletano, Flavia; Corkery, John M.; Kotzalidis, Georgios D. (Frontiers in Psychiatry, 2021)
Kratom or Mitragyna speciosa (Korth.) is an evergreen tree of the coffee family native to South-East Asia and Australasia. It is used by locals recreationally to induce stimulant and sedative effects and medically to soothe pain and opiate withdrawal. Its leaves are smoked, chewed, or infused, or ground to yield powders or extracts for use as liquids. It contains more than 40 compounds; among these, mitragynine, 7-hydroxymitragynine, and mitragynine pseudoindoxyl are endowed with variable mu, delta, and kappa opioid stimulating properties (with 7-hydroxymitragynine having a more balanced affinity), rhynchophylline, which is a non-competitive NMDA glutamate receptor antagonist, and raubasine, which inhibits α1-adrenceptors preferentially over α2-adrenceptors, while the latter are stimulated by mitragynine and 7-hydroxymitragynine, which are also 5-HT2A antagonists. This complexity of neurochemical mechanisms may account for kratom’s sedative-analgesic and stimulant effects. It is commonly held that kratom at low doses is stimulant and at higher doses sedative, but no cut-off has been possible to define. Long-term use of kratom may produce physical and psychological effects that are very similar to its withdrawal syndrome, i.e., anxiety, irritability, mood, eating, and sleep disorders, other than physical symptoms resembling opiate withdrawal. Kratom’s regulatory status varies across countries; in Italy, both mitragynine and the entire tree and its parts are included among regulated substances. We describe the case of a patient who developed anxiety and dysphoric mood and insomnia while using kratom, with these symptoms persisting after withdrawal. He did not respond to a variety of antidepressant combinations and tramadol for various months, and responded after one month of clomipramine. Wellbeing persisted after discontinuing tramadol.